Storage stability study of metronidazole and hydroxymetronidazole in chicken eggs by liquid chromatography tandem mass spectrometry - Mikhail Vokuev; Artem Melekhin; Anastasia Frolova; Anton Bairov; Igor Rodin; Victor Tishchenko (Food Chemistry: X)
Metronidazole (MNZ) is one of the most commonly used antibiotics in the food industry. High levels in food can lead to the development of antimicrobial resistance in humans, so it is important to monitor its levels in food. In the context of legal proceedings, it is frequently necessary to re-examine samples after an extended period of time. It is therefore crucial to ensure that the analytes in question do not degrade during the storage period. In this study, HPLC-MS/MS approach was validated and used to analyze levels of MNZ and its hydroxy metabolite in chicken eggs during storage in the refrigerator (+4 °C) and in the freezer (−20 °C) for 3 months. An analyte solution was administered to hens to obtain eggs containing MNZ and hydroxymetronidazole (MNZ-OH). The dependence of the analyte content in eggs as a function of time after sampling was also investigated.